Misdiagnosed amoebic colitis leading to severe dysentery and necrotizing colitis—Report of a case and review of the literature. (March 2014) - Mogensen, Trine H.; Christiansen, Jens J.; Eivindson, Martin V.; Larsen, Carsten S.; Tøttrup, Anders
Abstract We present a case of amoebic colitis, misdiagnosed as inflammatory bowel disease and treated with corticosteroids, leading to severe necrotizing enterocolitis. We review the literature on the epidemiology, pathogenesis, diagnosis, and treatment of amoebic dysentery, with special emphasis on the association between immunosuppressive treatment and the development of severe invasive amoebiasis.